LAPORAN KASUS: HIPOKALEMIA PERIODIK PARALISIS - Karlina Mahardieni; Diani Nazma; Christian Soesilo; Noviani Prasetyaningsih (Fakultas Kedokteran Universitas Trisakti, 2024)
Hypokalemic periodic paralysis is one form of rare periodic paralysis that can result in sudden weakness. Comprehensive examination is required to determine the management in such cases. This case report discusses a 26-year-old woman who presented to the hospital with a sudden complaint of weakness in all limbs and no neurological deficits. The patient had a history of being admitted three times in the past year with the same complaint. Laboratory results revealed significantly low potassium levels. Although rare, periodic paralysis must be promptly distinguished from other causes of weakness and paralysis. Immediate and appropriate actions are crucial. After rapid administration of potassium through a central vein, the limb weakness disappeared. The patient had a history of three admissions with severe hypokalemia. Abdominal ultrasound revealed mild right hydronephrosis. In this case, the patient fully recovered after receiving both oral and intravenous potassium supplementation with strict ECG monitoring in the ICU. The patient returned to the ward after 2 days in the ICU and was subsequently referred to a nephrology specialist for the management of the observed hydronephrosis. This is important to identify the underlying cause of recurrent hypokalemic paralysis